VAD related infections and the risk of pump thrombosis and thromboembolic events: a EUROMACS study. (14th October 2021) - Zijderhand, C.F; Antonides, C.F.J; Veen, K.M; Schoenrath, F; Gummert, J; Nemec, P; Merkely, B; Musumeci, F; Meyns, B; De By, T; Bogers, A.J.J.C; Caliskan, K
Abstract: Background: In patients supported by a ventricular assist device (VAD) major infections are a frequently reported adverse event with increased morbidity and mortality. Purpose: The purpose of this study was to investigate the possible association between infections and cerebrovascular accidents (CVAs) in VAD patients. Methods: An analysis of the European Registry for Patients Assisted with Mechanical Circulatory Support (EUROMACS) was performed identifying all patients aged ≥18 years with a LVAD or BiVAD implantation. Infections were categorized as VAD-specific infections, VAD-related infections and, non-VAD infections. An extended Kaplan-Meier analysis for the risk of CVA and mortality with infection as a time-dependent covariate was performed. Furthermore, a multivariable Cox proportional hazard model was performed including 24 variables. Results: For this analysis 3784 patients were included, with 45 patients being supported by a BiVAD and 3739 by an LVAD. The majority of patients were male (83.2%) and 60.5% had an INTERMACS patient profile 2 or 3. During follow-up, 3108 major infections were identified in 1385 (36.6%) of the patients, while 673 CVAs were identified in 545 (14.4%) of the patients. Extended Kaplan-Meier analysis with first infection as time-dependent covariate revealed a hazard ratio (HR) for CVA of 1.95 (95% CI: 1.57–2.36; p<0.005) (Figure) and 1.50 (95% CI: 1.33–1.68, p<0.005) for mortality. Multivariable analysis confirmed a significant association for infection and CVAs with a HR of 1.46 (95% CI: 1.29–1.64). With infections subcategorized, VAD-specific (HR: 1.57 (95% CI: 1.18–2.09)) and VAD-related infections (HR: 2.04 (95% CI: 1.44–2.89)) remained significantly associated with CVA but non-VAD infections (HR: 1.22 (95% CI: 0.92–1.64)) were not. Conclusion: Both VAD-related and VAD-specific infections are associated with a significantly increased risk of CVA with increased risk of mortality. Funding Acknowledgement: Type of funding sources: None.